# Functions machine help!Watch

Announcements
#1
Function 1 is given by y = x - 1 and function 2 is given by y = 3x^2.
Show that the equation for the composite function formed by function 1 followed by function 2 is the same as y = 3x^2 - 6x + 3.
Last edited by Soul Wavel3ngth; 3 days ago
0
3 days ago
#2
(Original post by Soul Wavel3ngth)
Function 1 is given by y = x - 1 and function 2 is given by y = 3x^2.
Show that the equation for the composite function formed by function 1 followed by function 2 is the same as y = 3x^2 - 6x + 3.
say f(x) = x-1 and g(x)=3x^2
essentially the question is asking how would g(f(x)) look like so:
3(x-1)^2
= 3(x^2-2x+1)
=3x^2 - 6x + 3
therefore y = 3x^2 - 6x + 3.
0
#3
So function machines aren't needed? Because it says "Function 1 followed by function 2". But your method seems reasonable so I guess i'll try that.
(Original post by SoCraZy)
say f(x) = x-1 and g(x)=3x^2
essentially the question is asking how would g(f(x)) look like so:
3(x-1)^2
= 3(x^2-2x+1)
=3x^2 - 6x + 3
therefore y = 3x^2 - 6x + 3.
0
3 days ago
#4
(Original post by Soul Wavel3ngth)
So function machines aren't needed? Because it says "Function 1 followed by function 2". But your method seems reasonable so I guess i'll try that.
you could use function machines I suppose though I see no reason to do so
0
X

new posts
Latest
My Feed

### Oops, nobody has postedin the last few hours.

Why not re-start the conversation?

see more

### See more of what you like onThe Student Room

You can personalise what you see on TSR. Tell us a little about yourself to get started.

### University open days

• London Metropolitan University
Tue, 21 May '19
• Brunel University London
Wed, 22 May '19
• University of Roehampton
Wed, 22 May '19

### Poll

Join the discussion

#### How has 2019 been so far?

Amazing!!! (56)
5.77%
Fairly positive (301)
31.03%
Just another year... (384)
39.59%
Is it 2020 yet? (229)
23.61%